Extinction Phenomena: A Biologic Perspective on How and Why Psychoanalysis Works - Brakel, Linda A. (Frontiers in Psychology, 2011)
This article presents the view that much of the success of classical psychoanalysis is centrally predicated on its biological potency; focusing not on neuropsychology, but on the biology of conditioning. The argument suggests that features of classic psychoanalytic technique--the couch, meetings several times per week with both parties present, and free association--uniquely facilitate intense transferences of various sorts, and that these in turn constitute the multiple and diverse extinction trials necessary to best approximate extinction.